Building an Online Community Through Research (Journal of Organizational Psychology, 2023)
One of the more complex things to do when becoming a new faculty is meeting the scholarship expectations of your role. A finished dissertation does not easily equate to a peer-reviewed publication later. What if we could give students the tools to embrace scholarship before graduating? This paper outlines a process for engaging online learners in research endeavors outside the course room. It also shows how this unique method can increase community and belonging among peers. The model presented here can be used for research and other community-based projects. While it is useful for faculty development, it is designed to benefit both experienced and new faculty. However, the primary purpose of this model is student development. This model is meant to give the students the skills and tools they need to become researchers on their own.
Keywords: organizational psychology; research in online programs; community building; faculty development